2014
DOI: 10.1117/1.jbo.19.7.077001
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz pulsed spectroscopy of paraffin-embedded brain glioma

Abstract: Abstract. The refractive indices, absorption coefficients, and complex dielectric constants of paraffin-embedded brain glioma and normal brain tissues have been measured by a terahertz time-domain spectroscopy (THz-TDS) system in the 0.2-to 2.0-THz range. The spectral differences between gliomas and normal brain tissues were obtained. Compared with normal brain tissue, our results indicate that paraffin-embedded brain gliomas have a higher refractive index, absorption coefficient, and dielectric constant. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 30 publications
6
63
0
2
Order By: Relevance
“…Therefore, TRI may serve as a high-sensitivity detector for glioma, allowing neurosurgeons to ‘see’ tumor regions without the use of contrast agents during glioma surgery. Several papers reported on the possibility of glioma detection using TRI234041. However they used only fresh rat or paraffin-embedded samples.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TRI may serve as a high-sensitivity detector for glioma, allowing neurosurgeons to ‘see’ tumor regions without the use of contrast agents during glioma surgery. Several papers reported on the possibility of glioma detection using TRI234041. However they used only fresh rat or paraffin-embedded samples.…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded tissues are frequently measured to reduce the influence of water, and numerous data revealed that cancer tissues display higher absorption coefficients ( Figure 2E) and refractive indexes than normal tissues [42,43]. However, cancerous gastric tissues exhibit higher absorption than normal tissues only at relatively low THz frequencies [44].…”
Section: Tissuesmentioning
confidence: 97%
“…(E) Absorption coefficients of paraffin-embedded brain gliomas (red) and normal tissues (black). Absorption coefficients of glioma tissue were higher than those of normal tissue at frequencies below 1 THz, although the differences were not distinct at higher frequencies [43]. All figure panels were adapted, with permission, from the references indicated.…”
Section: Noninvasive and Nonionizing Propertiesmentioning
confidence: 99%
“…THz spectroscopy has been applied to distinguish brain tumors 1214 and neurodegenerative disorders, such as Alzheimer’s disease 15, 16 , but it probably more apply to myelin-associated disease. In 2004, with continuous-wave THz imaging technique, Darmo et al .…”
Section: Introductionmentioning
confidence: 99%